Reminder for consequences of obstructing execution of a public works project undertaken by the Government of Bangladesh as well as obstructing the employer to get power supply to run the BRAC University new campus project - Brac University (Brac University, 2023)
This record consists of general correspondence regarding reminder for consequences of obstructing execution of a public works project undertaken by the Government of Bangladesh as well as obstructing the employer to get power supply to run the BRAC University new campus project.